Sangkan Paraning Dumadi: The Image of Women, Hysteria, and Patriarchal Chains in Intan Paramadhita’s Short Story - Rodliatul Amaliah; Novia Adibatus Shofah; Choirunnisa Salwa Tawakal (Program Studi Sastra Indonesia UIN Sunan Ampel Surabaya, 2022)
This study focuses on the psychological symptoms experienced by the Mother in Pemintal Kegelapan (The Dark Spinner) by Intan Paramadhita. Hysteria is understood as a neurosis form based on an element of anxiety in the character’s past life. Psychological disorders in the short story can be seen from the dual personality of the Mother to avoid or cure the anxiety she suffers. As a psychological disorder, hysteria certainly has a therapy known as catharsis. That method is applied by the Mother as a treatment for her psychological disorders. The feminist reflection of Pemintal Kegelapan can be analyzed by applying Sigmund Freud’s psychoanalytic theory. Through that stage of analysis, it can be known how the Mother applies the cathartic method. The causes of the hysteria disorder experienced can be revealed, both hysteria as a mental illness and a woman’s disease.